Influence of catheterization on the prostate specific antigen level in patient suffering from prostate disorder - Osman Sianipar Osman Sianipar (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Background: The increase of life expectancy may increase the number of patients suffered from prostate disorder. In Indonesia prostate cancer is in the top ten malignancies in men and is the second most frequent malignancies in urology clinics. Early detection may decreasies its fatality rate and increase the quality of life. Prostate specific antigen (PSA) is clinically the most useful tumor marker; its serum level has positive correlation with the prostate cancer. Serum PSA level will also increase in inflammation, benign prostate hyperplasia (BPH) and interventions like catheterization, digital rectal examination and biopsy.Objective: The objective of this study is to examine the catheterization effect for the result of PSA test in patients with prostate disorder.Methods: Subjects of study are all of patients who present symptoms related prostate. Venous blood samples are taken using aseptic technique then processed further to collect serum. Level of PSA is determined by ELISA technique from the serum. Study population is grouped according to result of histopathologist examination namely benign prostate hypertrophy, benign prostate hypertrophy with prostatitis, benign prostate hypertrophy with prostate intraepithelial neoplasm and prostate cancer. In addition, patients are also grouped into group that already catheterized and those who have not been catheterized before blood sample was taken. One-way ANOVA and Pearson correlation were used to analyse the effects.Result: Mean of PSA level in patients sufferring from benign prostate hypertrophy, benign prostate hypertrophy with prostatitis, benign prostate hypertrophy with prostate intraepithelial neoplasm respectively were 17.61 ng/mL, 17.33 ng/mL and 19.77 ng/mL. This was significantly different compared to those in the same group but without catheterization before blood collection. Mean of PSA level in prostate cancer patient was 38.3 ng/mL. It was not significantly different to those in prostate cancer patient but without catheterization before blood collection.Conclusion: Urine catheterization prior to determination of PSA level showed an effect to increase PSA level in the group of patients presenting complain of related prostate but it is not found in protate cancer patient.Key words: PSA - prostate disorder - prostate cancer - catheterization